The work-family interface : spillover, complications, and challenges - Blair, Sampson Lee; Obradović, Josip (Contemporary perspectives on family research ;, 2018)
Family researchers have long recognized the interconnected nature of work and family. Around the globe, there is a clear recognition that the paid labor experiences of individuals will affect their families and familial relationships, often in unanticipated ways. Likewise, family relationships and family structures can significantly influence the work experience of individuals. As experiences of both families and work vary considerably across cultures, and over time, the nature of the work-family interface continues to change. The work-family interface impacts not only adults within families, but also children, and the interwoven nature of work and family yields significant consequences for all family members and relationships. In order to better understand these issues, this multidisciplinary volume addresses such topics as: parental employment and parenting, paid labor and marital quality, the integration of work-family domains, childcare and child development, dating and mate selection at work, work stress and family violence, health consequences of work-family conflict, relationship roles among dual-earner couples, family determinants of job performance, gender differences in work-family demands and consequences, and work stressors and family functioning; among others. The chapters in this volume provide substantial insight into our understanding of the work-family interface, and provide meaningful directions for both future research and policy.